Nhakanomics harvesting knowledge and value for re-generation through social innovation - Lessem, Ronnie; Mawere, Munyaradzi; Taranhike, Daud (Masvingo, Zimbabwe : Africa Talent Publishers, 2019)
Nhakanomics: Harvesting Knowledge and Value for Re-generation Through Social Innovation is a radical departure from the commonly held belief that neo-liberal economics from the US and the West is universal, and is the only solution to underdevelopment and poverty throughout the world. Instead, the book teases out and theorises the intellectually rutted terrain of development studies, and neo-liberal economics from a decolonial Pan-Africanist perspective. Following a path of social innovation, with perspectives drawn from social anthropology, economics, and business and management studies Nhakanomics is a unique socio-economic approach applicable in the Global South and in Southern Africa in particular. The study argues that the process and substance of nhakanomics with its pre-emphasis on the relational South provides a robust and holistic approach to social innovation and social transformation grounded in relational networks and 'meshworks'. The central idea is a call to re-GENE-rate society, through local Grounding and Origination, and tapping into local-global Emergent Foundations via a newly global Emancipatory Navigation, while ultimately culminating in global-local transformative Effects in four recursive cycles of re-GENE-rating C(K)umusha, Culture, Communication, and Capital after re-Constituting Africa-the 5Cs. With a novel and radical approach the book is an interrogation of neo-liberal economics in the Global South. As such, this book is remarkably handy to students and practitioners in the fields of economics, development studies, political science, science and technology studies, business management, sociology, transformation studies, and development related non-Governmental Organisations working with grassroots communities.
CHAPTER 6 -- INTEGRAL KUMUSHA -- COMMUNITY/LABORATORY, OIKOS TO KUMUSHA -- 6.1. Introduction: Buhera -- 6.2. Self Sufficiency to Developmental Economy -- 6.2.1. Communal and Economic Exchange -- 6.2.2. Oikos, Polis and Household Management -- 6.2.2. Main Features of a New Subsistence Paradigm -- 6.2.3. Restoring the Link Between the Market and Subsistence -- 6.2.4. From Labor to Work and Fulfillment -- 6.3. Integral Kumusha Concept -- 6.3.1. To Preserve, Restore and Enhance Zimbabwe's African Nhaka -- 6.3.2. Overturning the Buhera Label as "A Place for the Poor" -- 6.3.3. The "Nhaka" Concept and Enterprises Underlying Integral Kumusha -- 6.4. The Journey to Creating the Buhera Integral Kumusha -- 6.4.1. Our Nhaka involves CARE-ing for our Ancestors -- 6.4.2. Community Activation Towards the Integral Kumusha -- 6.4.3. Awakening Integral Kumusha Consciousness -- 6.4.4. Institutionalised Innovative Research: Involving Local Schools -- 6.4.5. Embodiment of the Transformation -- 6.5. Conclusion: Kumusha, Communitalism, Nhakanomics -- 6.5.1. Common Future to African Future -- 6.5.2. Nature Power, Communitalism and Nhakanomics -- 6.5.3. Psychology is for Back-Room Boys -- 6.6. References -- 2nd CYCLE SPIRITUAL GROUNDING: RE-GENE-RATE CULTURE -- CHAPTER 7 -- HURUDZA: WATER AND SOIL IN HOLY "MATRIMONY" -PILGRIMIUM/COMMUNITY -- 7.1. Introduction: Land and Liberation -- 7.1.1. Appear to Learn Nothing and Forgot Nothing About the Errors of their Ways -- 7.1.2. Situated Reason -- 7.1.3. Going Back to the Land Question -- 7.2. Shona Cosmology of Water, Soil and Marriage -- 7.2.1. Women are Associated with Fertility and Land -- 7.2.2. Full of Sound and Fury: The Climate Change Discourse -- 7.2.3. Thou Should Not Only Survive but Thrive if ... -- 7.3. Moving Along His Own Trajectory -- 7.3.1. Water and Soil in a Holy Matrimony.
eBooks on EBSCOhost
Keywords: Community development -- Africa, Southern; Economic development -- Social aspects -- Africa, Southern; Social systems; Systèmes sociaux; Développement communautaire -- Afrique australe; Modern & contemporary fiction (post c 1945); BUSINESS & ECONOMICS / Development / Sustainable Development; SOCIAL SCIENCE / Developing & Emerging Countries; Community development; Economic development -- Social aspects; Social systems; Southern Africa; Sozialer Wandel; Entwicklungsmodell; Alternative Wirtschaftspolitik; Subsaharisches Afrika